Cultural Hybridity in Indonesian Contemporary Cinema: A Postcolonial Study on the Film Bumi Manusia - Fajar, Yusri (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2024)
Colonialism has profoundly engulfed the cultural, social, and political aspects of Indonesian society. Indigenous people have responded to its legacy by movements, negotiating their identity, and engaging in cultural appropriation. This article analyses the portrayal of cultural hybridity in the film Bumi Manusia which was directed by Hanung Bramantyo and released in 2019. In particular, this paper investigates how indigenous and Indo-European people navigate their identities through the adoption of distinct cultural practices. Subsequently, this article examines their challenges when engaging in cultural hybridity. The research is qualitative with the critical paradigm and employs the theory of cultural hybridity. The research findings indicate that pivotal indigenous figures and an Indo-European decent negotiate their identities by engaging in both indigenous and European cultural practices. This is evident in their adoption of language, attire, food, and tradition. They aimed to adjust to a diverse colonial society and achieve self-empowerment and resistance through negotiations and practices. However, their engagement in cultural hybridity encounters both approval and rejection.